Swachh Bharat Abhiyan: Creating a Clean India: The Swachh Bharat Abhiyan Movement (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Swachh Bharat Abhiyan launched on October 2, 2014 by Prime Minister Narendra Modi, in the memory of Mahatma Gandhi to create a clean India of his dreams by 2019, his 150th birth anniversary. The objectives of Swachh Bharat include eliminating open defecation through the constructing 12 million toilets in rural India at a projected cost of rupees 1.96 lakh crores, community toilets and solid waste management.The Prime Minister has spread the message by his priceless words. People From different sections of society like from government official to Jawans, Bollywood actors to the sportspersons, industrialist and millions of people across the country have come move forward and join mass movement of cleanliness. It is that project in which all people participated by their own as mission. A swachh bharat mission includes many issues especially open defecation and sanitation issue.